2011
DOI: 10.1007/s11357-011-9323-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity contributes to abnormalities in pain behaviors between young and old rats

Abstract: Aging has profound yet unpredictable effects on pain perception and incidence of anxiety disorders. However, the mechanisms underlying age-related pathologies are confounded by contradictory observations in rodent models. Therefore, the goal of our study was to test the hypothesis that genetic variability contributes to age-related pain behaviors and susceptibility to anxiety. To address this hypothesis, we examined pain and anxiety-like behavior in young or old Brown Norway (BN), Fisher 344, and BN/F344 (F1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…For example, one study comparing 6- and 26-month-old rats showed that although young Brown Norway rats displayed lower von Frey thresholds than older ones, the pattern was reversed in Fischer 344 rats. 1 …”
Section: Discussionmentioning
confidence: 99%
“…For example, one study comparing 6- and 26-month-old rats showed that although young Brown Norway rats displayed lower von Frey thresholds than older ones, the pattern was reversed in Fischer 344 rats. 1 …”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of this rodent model is that we were able to examine the long‐term consequences of ELS at a defined stage in adulthood. In the current study, we selected to investigate nociceptive and anxiety‐like behaviors in adulthood, at a carefully controlled time point, specifically at PND 90 to reduce potential age‐related changes in nociceptive behaviors across the rodent life span, and to ensure that all females had reached full maturity. However, a limitation of the current study is that we studied only the activational effects of ELS.…”
Section: Discussionmentioning
confidence: 99%
“…However, this interpretation is not without complication due to cultural and environmental differences. In the more controlled preclinical environment, distinct differences in pain responsiveness between strains indicate a definite role for genetic variation in pain perception . Between males and females, obvious genetic differences may also play a role in pain sensitivity and vulnerability or resilience to certain types of stress‐induced chronic pain …”
Section: Vulnerability and Resilience To Stress‐induced Painmentioning
confidence: 99%